Mice lacking Axl and Mer tyrosine kinase receptors are susceptible to experimental autoimmune orchitis induction. Issue 3 (18th November 2014) - Li, Nan; Liu, Zhenghui; Zhang, Yue; Chen, Qiaoyuan; Liu, Peng; Cheng, C Yan; Lee, Will M; Chen, Yongmei; Han, Daishu
Abstract : The mammalian testis is an immunoprivileged organ where male germ cell autoantigens are immunologically ignored. Both systemic immune tolerance to autoantigens and local immunosuppressive milieu contribute to the testicular immune privilege. Testicular immunosuppression has been intensively studied, but information on systemic immune tolerance to autoantigens is lacking. In the present study, we aimed to determine the role of Axl and Mer receptor tyrosine kinases in maintaining the systemic tolerance to male germ cell antigens using the experimental autoimmune orchitis (EAO) model. Axl and Mer double‐knockout (Axl −/− Mer −/− ) mice developed evident EAO after a single immunization with germ cell homogenates emulsified with complete Freund's adjuvant. EAO was characterized by the accumulation of macrophages and T lymphocytes in the testis. Damage to the seminiferous epithelium was also observed. EAO induction was associated with pro‐inflammatory cytokine upregulation in the testes, impaired permeability of the blood–testis barrier and generation of autoantibodies against germ cell antigens in Axl −/− Mer −/− mice. Immunization also induced mild EAO in Axl or Mer single‐gene‐knockout mice. By contrast, a single immunization failed to induce EAO in wild‐type mice. The results indicate that Axl and Mer receptors cooperatively regulate the systemic immune tolerance to male germ cell antigens.